A two-stage OGI approach to compute the regional competitiveness index. Issue 2 (18th March 2019) - Charles, Vincent; Sei, Tomonari
Abstract : Purpose: Regional competitiveness refers to the capacity of a region to manage its resources and competencies to increase the well-being of its people. Measuring regional competitiveness is, thus, a major consideration for policymakers, businesses and the academic community in their endeavour to improve the same. This paper aims to demonstrate a novel way to calculate the regional competitiveness index under a two-stage objective general index (OGI) framework. Design/methodology/approach: The authors compute the regional competitiveness index under a two-stage OGI framework. In the first stage, they aggregate the sub-factor level information into a factor level index; in the second stage, they use the factor level index to obtain a regional competitiveness index. Findings: The authors discuss the properties of the proposed index in detail. They further analyse five periods of regional competitiveness of Peru spanning the period 2008-2015. Among others, the results reveal the existence of the resource curse of the mining regions of Peru. Practical implications: The paper is a contribution to the practical measurement of competitiveness. Social implications: The calculation of a regional competitiveness index is vital for improving the competitiveness of the countries and for reducing regional inequalities. Originality/value: When compared to the existent methods available in the literature, the advantage of the proposed method resides in the fact that the derived index has a positive correlation with the factor-level indices and the factor-level indices have a positive correlation with the sub-factor-level information.